Pemberdayaan Karir Guru di Kecamatan Alas, Sumbawa: Strategi Peningkatan Kompetensi dan Peluang Profesional - Gunawan Gunawan; Kosim Kosim; Muhammad Zuhdi; Muhammad Taufik; Satutik Rahayu (Indonesian Publication Center, 2025)
Teacher career development is a key factor in improving the quality of education. However, teachers in regional areas often face challenges related to accessing information and scientific publication skills. This community service (sercom) activity aimed to empower teachers through comprehensive training focused on strategies for enhancing their competency and professional opportunities. The methods used included interactive training, discussions, and question-and-answer sessions. The activity received a positive response from teachers at SMAN 1 Alas, with a significant increase in their understanding of various aspects of career development. The main outputs of this activity were an improved understanding among teachers regarding career strategies, advanced study opportunities, and publication tips. Additionally, this activity successfully built a strong collaborative network between teachers, the sercom team, and publication partners, which has the potential to further support teacher career development. It is concluded that career training and guidance have a significant positive impact on teacher competency and their understanding of career opportunities in Alas Subdistrict.